2014
DOI: 10.3989/redc.2014.3.1112
|View full text |Cite
|
Sign up to set email alerts
|

Retos y oportunidades en organización del conocimiento en la intersección con las tecnologías de la información

Abstract: Cómo citar este artículo/Citation: Martínez-Ávila, D.; San Segundo, R.; Zurian, F. A. (2014). Retos y oportunidades en organización del conocimiento en la intersección con las tecnologías de la información. Revista Española de Documentación Científica, 37(3):e053. doi: http://dx.doi.org/10.3989/redc.2014.3.1112Resumen: En este trabajo se estudia la intersección de la Organización del Conocimiento y las Tecnologías de la Información, haciendo especial incidencia en los retos y oportunidades que existen en este … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Regarding the impact of social influence on trust, in a new technology, trust must be won over time and experience [53]. However, due to social influence, the time normally required to develop confidence in a new technology may be shortened [49].…”
Section: Hypothesis 4 (H4) Facilitating Conditions Would Have a Posimentioning
confidence: 99%
“…Regarding the impact of social influence on trust, in a new technology, trust must be won over time and experience [53]. However, due to social influence, the time normally required to develop confidence in a new technology may be shortened [49].…”
Section: Hypothesis 4 (H4) Facilitating Conditions Would Have a Posimentioning
confidence: 99%
“…The scope of KO, as an interdisciplinary field, seems to be in-between the social sciences and humanities, interested in aspects related to veracity and value, and the Semantic Web Community. Several studies within the KO community (e.g., Smiraglia, 2012;Martínez-Ávila et al, 2014;Martínez-Ávila, 2015) have identified LOD as an emerging and key trend for the future of KO. Shiri (2014, p. 19) also claimed that "Big data organization, representation and visualization will be among the emerging areas or research that information organization research will have to address."…”
Section: Discussionmentioning
confidence: 99%
“…Esto permitirá a largo plazo mejorar la experiencia informacional de las personas usuarias en las bibliotecas y centros de recursos (Gonzales, 2014), concediendo a los usuarios el implacable valor que representan como unidades de información y acervos de conocimiento al lado de los procesos de modernización tecnológica. De esta forma, se considera que tales iniciativas promueven el fortalecimiento de la web como producto social, que utiliza la inteligencia colectiva interconectada (Martínez-Ávila et al, 2014) para el fortalecimiento de las competencias.…”
Section: Revistaebci@ucraccrunclassified